WORKSHOP PLAYMAKER UNITY UNTUK SISWA SMA SINAR DHARMA - Haris, Darius Andana; Salim, Hansen; Kristianto, Joseph (Jurnal Serina Abdimas, 2024)
The advancement of information and communication technology is also an important factor that helps in many ways. Everything that happens online further encourages the advancement of information and communication technology. Game development using Unity is one form of information and communication technology product. Due to the rapid development and popularity of game development, game development has become a separate institution in some educational institutions. At the school level, especially at the high school level, game development can be learned through workshop activities. Workshop activities allow high school students to more quickly develop their potential and utilize the knowledge gained in preparation for the next world of higher education and also add non-academic abilities. This workshop activity also serves as a forum to help students improve their non-academic results. The expected achievement has reached the target, with students successfully understanding the basics of game development using Unity. With this success, it is possible to bring a positive impact to the educational environment to create more interest in technology. Similar PKM has already been implemented in extracurricular classes and received a positive response. SMA Sinar Dharma, which has previously won competitions conducted through PKM, has now started the Unity Basic extracurricular. The PKM implementation is divided into several stages: needs assessment, material development, and workshop implementation. Thus it can be concluded that this activity went well, had a positive impact on both parties, providing non-academic skills. ABSTRAK Kemajuan teknologi informasi dan komunikasi juga menjadi faktor penting yang membantu dalam banyak hal. Segala sesuatu yang terjadi secara online semakin mendorong kemajuan  teknologi informasi dan komunikasi. Pengembangan game menggunakan Unity merupakan salah satu bentuk produk  teknologi informasi dan komunikasi. Karena pesatnya perkembangan dan popularitas pengembangan game, menjadikan pengembangan game sebuah instansi tersendiri di beberapa instansi pendidikan. Di tingkat sekolah, khususnya di tingkat menengah atas, pengembangan permainan dapat dipelajari melalui kegiatan lokakarya. Kegiatan lokakarya memungkinkan siswa SMA untuk lebih cepat mengembangkan potensinya dan memanfaatkan ilmu yang didapat sebagai persiapan menghadapi dunia pendidikan tinggi selanjutnya dan juga menambah kemampuan non-akademik. Kegiatan lokakarya ini juga berfungsi sebagai wadah  untuk membantu mahasiswa meningkatkan hasil non-akademiknya. Pencapaian yang diharapkan sudah mencapai target, dengan siswa/i berhasil memahami dasar-dasar pengembangan game menggunakan Unity. Dengan keberhasilan ini memungkinkan untuk membawa dampak positif ke lingkungan pendidikan untuk menciptakan minat yang lebih terhadap teknologi. PKM serupa sudah pernah dilaksanakan di kelas ekstrakurikuler dan mendapat respon positif. SMA Sinar Dharma yang sebelumnya pernah menjuarai lomba-lomba yang dilakukan melalui PKM, kini telah memulai ekstrakurikuler Unity Basic. Pelaksana PKM dibagi dalam beberapa tahap: pengkajian kebutuhan, pengembangan materi, dan pelaksanaan lokakarya. Dengan demikian dapat disimpulkan bahwa kegiatan ini berjalan dengan baik, memberikan dampak positif untuk kedua belah pihak, memberikan kemampuan non-akademik.